Terminological Variation in Source Texts and Translations: A Pilot Study - Fernández-Silva, Sabela; Kerremans, Koen (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
In this article, it is assumed that the choice of terminological variants in specialized source texts is sometimes cognitively motivated and that this motivation is reflected in the choice of equivalents in the target texts. On the basis of a pilot study, we will present a method for comparing the cognitively motivated terminological variants in source texts and their translations. The corpus in the pilot study is composed of three Galician source texts and their English translations. The texts are scientific articles addressing the economic effects of environmental disasters on fisheries. A quantitative study was first carried out in which the number of unique terms in each source text was compared to the number of unique translations of these terms. Next, each unique combination of a source term and its translation equivalent was subjected to a qualitative analysis. A value was manually assigned in order to qualify the “cognitive distance” between the source term and its translation. Based on these values and the frequency of the translation pair in each bitext, we computed the “interlingual variation index” (IVI). Differences in results between the bitexts are linked to extra-linguistic factors related to the translation processes.